(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
Abstract: Tensions lead to the disruption of diplomatic relations between countries due to disputes that may arise between them, which can lead to the closure of diplomatic channels of communication, which represent the ideal tool for resolving outstanding issues, protecting the interests and develop diplomatic relations, and the tension can lead to the collapse of bilateral relations if the dispute is confined between two countries. This type of situation requires the innovation of contacts and friendly communication between countries within the framework of diplomatic channels and therefore it is very important to know the factors that create tensions. Knowing the nature of these factors obviously leads to circumventing them and avoiding their negative consequences. Keywords: Diplomatic communication, Freedom of communication, Diplomatic immunities, Diplomatic envoy, Diplomatic correspondence.